2012
DOI: 10.1186/1471-2148-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Bactrocera dorsalis s.s., B. papayae and B. philippinensis (Diptera: Tephritidae) in southeast Asia: evidence for a single species hypothesis using mitochondrial DNA and wing-shape data

Abstract: BackgroundBactrocera dorsalis s.s. is a pestiferous tephritid fruit fly distributed from Pakistan to the Pacific, with the Thai/Malay peninsula its southern limit. Sister pest taxa, B. papayae and B. philippinensis, occur in the southeast Asian archipelago and the Philippines, respectively. The relationship among these species is unclear due to their high molecular and morphological similarity. This study analysed population structure of these three species within a southeast Asian biogeographical context to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 63 publications
(89 reference statements)
12
100
2
1
Order By: Relevance
“…We believe that in addition to previously reported differences between these species (e.g., pheromone composition), especially for B. carambolae, that behavioral variation (e.g., differences in mating location) contribute to the mating incompatibility observed here between B. carambolae and the remaining three species. While these data alone cannot be used to redeÞne species limits or to assert full sexual compatibility (because of the absence of full postzygotic testing; not completed in this study yet underway) and the inherent caveats of artiÞcial cage studies (Walter 2003), we consider our results closely parallel previous research suggesting that B. dorsalis, B. papayae, and B. philippinensis represent the same biological species (Medina et al 1998, Wee and Tan 2000b, Tan 2003, Krosch et al 2013, Schutze et al 2012. Such an outcome has signiÞcant implications not only for their taxonomic identities, but has consequences for pest management (especially for the SIT for which knowledge of species limits and mating compatibility are critical) and international trade.…”
Section: Discussionsupporting
confidence: 85%
“…We believe that in addition to previously reported differences between these species (e.g., pheromone composition), especially for B. carambolae, that behavioral variation (e.g., differences in mating location) contribute to the mating incompatibility observed here between B. carambolae and the remaining three species. While these data alone cannot be used to redeÞne species limits or to assert full sexual compatibility (because of the absence of full postzygotic testing; not completed in this study yet underway) and the inherent caveats of artiÞcial cage studies (Walter 2003), we consider our results closely parallel previous research suggesting that B. dorsalis, B. papayae, and B. philippinensis represent the same biological species (Medina et al 1998, Wee and Tan 2000b, Tan 2003, Krosch et al 2013, Schutze et al 2012. Such an outcome has signiÞcant implications not only for their taxonomic identities, but has consequences for pest management (especially for the SIT for which knowledge of species limits and mating compatibility are critical) and international trade.…”
Section: Discussionsupporting
confidence: 85%
“…Testing was done without atp6 due to high rate of evolution in study (N 0.5). Even the recent molecular evidence also suggests that B. papayae, B. philippinensis, B. invadens and B. dorsalis represent one species (Krosch et al, 2013;Schutze et al, 2012Schutze et al, , 2015Jose et al, 2013;Boykin et al, 2014) which has also been confirmed by the phylogeny based on PCGs and rRNAs of mitogenomes in the present study. Supplementary data to this article can be found online at http://dx.…”
Section: Phylogenetic Relationshipssupporting
confidence: 85%
“…Similarly, the biological status of members of B. dorsalis complex - B. dorsalis s.s., B. papayae , and B. phillipinensis - has recently been analyzed using independent multiple approaches such as studying several genes of mitochondrial DNA, microsatellite markers, and mating competitiveness [13-16]. This evidence suggests that they are the same entity.…”
Section: Introductionmentioning
confidence: 99%